The Politics and Symbolism of the #ThisFlag in Zimbabwe (The Strategic Review for Southern Africa, 2020)
In the context of the hashtag movement #ThisFlag, this paper examines the sensual affects drawn from flag symbolism and why the Zimbabwean flag is policed by the state. It uses the symbolism and politics of the hashtag movements by focusing on Evan Mawarire’s national lament and the Zimbabwean flag. It employs a literary and discursive analysis of Mawarire’s lament using desktop research on the contestations surrounding the flag. It shows that in dominant nationalist discourses, the flag is imaged as the land/nation and feminised to warrant it utmost respect, protection, sanctity and re/productive capacity. On the other hand, the #ThisFlag has made use of the flag to resist and subvert grand and naturalised dominant discourses of nationalism and citizenship to foster new imagi/nations of the nation. The use of the flag by the movement provoked ZANU-PF’s ownership of the national flag, which is quite similar to and has been drawn from the flag of the party, hence the movement was challenging the identity of the party, its ownership and its relevance. The paper shows the fluidity of symbols and symbolic meanings and why #ThisFlag had symbolic radical power and the possibilities of using the state’s and ZANU-PF’s cultural tools to challenge ZANU-PF’s hold on national knowledge and power. It contributes to our understanding of both state-power retention and how subaltern voices can uncover the agency of subjects within the very instruments of control incessantly used by dominant regimes.